Does Islamic More Efficient Than Conventional Life Insurance Performance During 2014-2021? - Herry Subagyo (Faculty of Economics and Business Universitas Jenderal Soedirman, 2022)
The research aims to analyze and comparisons of the efficiency of islamic and conventional life insurance in Indonesia. The research method uses a quantitative Data Envelopment Analysis (DEA) non-parametric approach to an assumption of Constant Return to Scale (CRS) and Variable Return to Scale (VRS) with input-output orientation. The sample used is three islamic life insurance and three conventional life insurance, which the sample criteria specified during 2014-2021. The input variables used are commissive costs, operating costs, and total equity, while the output variables are premium and investment income. The research results show that the economic efficiency value of Conventional Life Insurance is 64.82 percent, the technical efficiency is 72.22 percent, and the efficiency scale is 81.4 percent. While in Islamic Life Insurance, the economic efficiency value is 17.26 percent, the technical efficiency was 53.71 percent, and the efficiency scale was 47.41 percent. The different factors of efficiency level between conventional life insurance companies and islamic life insurance companies are the consumer's ease of use of the insurance products supported by optimal input to output management. The results of this research must be the main topic by islamic life insurance companies in planning the economic efficiency values and the company's technical operations in the future.